Palm-O-Lite: palm oil based aerosol for culinary applications - Izan Izwan, Misnon; Saifful Kamaluddin, Muzakir; Nazikussabah, Zaharudin; Muhmmad Nor, Omar (2018)
Malaysia is producing about 39% world palm oil production with nearly 15.4 million tons annually. The palm oil is not only rich with carotenoids, it also one of vitamin E source, helpful for prevention of oxidative deterioration. Currently, many down-stream products from this oil has been study including production of foods & beverages, cosmetics, healthcare and biodiesel. As another alternative to increase palm oil added value, the utilization of the oil in culinary field is presented in this work. The palm oil is formulated as cooking aerosol specifically for light cooking, baking, barbeque and grill. The light cooking and baking formulation is applied to culinary utensils as anti-sticking agent and minimization for usage of fats. The barbeque and grill are two seasoning aerosol for foods in order to enhance flavors and presentation of the dishes. The product is foreseen to be applied in home kitchen, picnic & outdoor and hotels as a clean and helpful culinary assistance.